Review on passive daytime radiative cooling: Fundamentals, recent researches, challenges and opportunities - Bijarniya J.P.; Sarkar J.; Maiti P. (My University, 2025)
Passive radiative sub-ambient cooling is an emerging field of futuristic research and development and has the potential to reduce water and electricity demands, and the negative environmental effects of conventional cooling systems. Nighttime radiative passive cooling was achieved even long before, and daytime passive radiative cooling has gained recent momentum in cooling technology due to the development of metamaterials. In this paper, materials of passive radiative cooling are described with fundamental physics applied to the interaction between the material and electromagnetic wave and material design. Structure of material is an important parameter to achieve daytime radiative cooling and hence three major material structure categories (multilayer structure, porous polymer, and randomly distributed structure) are discussed. Subsequently, the various fabrication processes and characterization of metamaterials for daytime radiative cooling are also described. Effects of various environmental factors like ambient temperature, cloud cover, moisture, pollution, wind velocity on radiative cooling performances are also discussed. The potential applications such as water cooling, space cooling, power plant condenser cooling, solar panel cooling and spacecraft cooling are described. Finally, various challenges of daytime radiative cooling are discussed and subsequently, future recommendations are provided, which may be useful for further research and development in this field. © 2020 Elsevier Ltd